Mental Health, the COVID-19 Pandemic and Social Inequalities: An Integrative Review - Mattoso, Beatriz Guedes; de Paiva, Fernando Santana; Coldibeli, Larissa Pimenta; Faria, Nicole Costa; Lima, Tiago Tavares (Revista PsicoFAE: Pluralidades em Saúde Mental, 2025)
The Covid-19 pandemic has had a significant impact on mental health conditions for different social groups, as it has contributed to worsening health inequalities. The aim of this work was to identify what has been researched nationally and internationally about the effects of the COVID-19 pandemic on mental health, considering the contexts of social inequalities experienced by different subjects and social groups. This paper is a literature review based on searches for articles indexed in the Virtual Health Library (VHL) between 2020 and 2022. The Boolean operator "and" was associated with the descriptors social inequality, mental health and Covid-19. Twenty-five articles from different countries were analyzed. The results reveal different conceptions and approaches used to classify expressions of mental health among different subjects and social groups, and the markers of gender and race linked to worse mental health conditions. Based on the experience of the pandemic, we consider the need to broaden our conceptions of mental health, as well as sociocultural differences, and factors such as food insecurity, poverty, gender and racial inequalities as essential in the production of mental health care practices.